Inhibitory Effect of TREK Channel Blockers on Sperm Viability and Motility of Korean Native Bull - Dawon Kang; Eun-Jin Kim; Jaehee Han (The Korean Society of Animal Reproduction and Biotechnology, 2017)
Antioxidants have been added to cryoprotectant or in vitro culture medium for sperm to reduce the detrimental damage, such as reactive oxygen species. However, curcumin, an antioxidant, shows dual effect on the viability and progressive motility of bovine sperm exposed to hydrogen peroxide. Low concentration of curcumin increases sperm viability and progressive motility, whereas high concentration of curcumin reduces them. This study was performed to identify whether TREK-1 channel is related to low sperm viability and motility induced by high concentration of curcumin. Curcumin reduced TREK-1 channel activity in a dose-dependent manner. TREK-1 channel was expressed in sperm obtained from Korean native bull. Treatment with TREK-1 channel blockers, such as curcumin, fluoxetine, GdCl3, and spadin, significantly reduced sperm viability and motility (p < 0.05). However, TREK-1 channel activators showed different effect; linoleic acid showed an increase in sperm viability and motility, and wogonin did not affect them. These results show that TREK-1 channel is involved in the regulation of sperm viability and motility. In particular, high concentration of curcumin might reduce sperm viability and progressive motility of Korean native bull through blockage of TREK-1 channel.